Molecular analyses reveal two lineages under the name Rimapenaeus constrictus (Stimpson, 1874) (Decapoda, Dendrobranchiata, Penaeidae) - Cardoso, Irene; Terossi, Mariana (Zootaxa, 2022)
The genus Rimapenaeus Pérez Farfante & Kensley, 1997 occurs in shallow waters and includes six species, being four restricted to Pacific Ocean and two restricted to Atlantic Ocean. Along the Brazilian coast, Rimapenaeus constrictus (Stimpson, 1874) (called camarão ferrinho in Brazil) is one of the species most often accidentally caught during fishery activities, but due to its small size and abundance, it is not commercially exploited. Considering its wide distribution in the western Atlantic the purpose of this study was to examine from a molecular and morphological perspective specimens identified as R. constrictus sampled at the two extremes of its distribution (USA and southeastern Brazil). The phylogenetic trees (16S mtDNA and Cytochrome oxidase subunit I genes) showed a split of these specimens in two well-supported lineages: lineage A from USA (Maryland, Virginia, Florida and Gulf of Mexico) and lineage B from southeastern Brazil (Rio de Janeiro and São Paulo). The genetic distance observed between them (16S: 3.2%; COI: 9.4%) is high to be intraspecific, mainly when compared with other Dendrobranchiata studied. Instead of it none clear pattern that allows the morphological separation of these lineages was observed. We conclude that the shrimps usually called of Rimapenaeus constrictus, widely distributed in the Atlantic, actually represents two species and the Brazilian lineage probably is a new species, not described yet.